2020
DOI: 10.18332/tid/128319
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette use behaviors and device characteristics of daily exclusive e-cigarette users in Maryland: Implications for product toxicity

Abstract: INTRODUCTION Few studies to date have characterized daily exclusive e-cigarette users, device characteristics, and use behaviors. This study describes daily e-cigarette user characteristics, and assesses the association between user behaviors and demographics. METHODS From 2015–2017, 100 daily exclusive e-cigarette users and 50 non-users were recruited in Maryland, USA. Sociodemographic characteristics, health status, e-cigarette/tobacco use behaviors, device characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…All the measured iAs concentrations in this study exceed the CalEPA REL; however, this REL represents continuous exposure, in contrast to the intermittent nature of vaping. The FDA sets permissible daily exposure (PDE) limits for elemental impurities in inhalation medications, in units of µg/day, which can be converted to concentration units of µg/g by dividing by daily dose in grams [28] . MOD e-liquid consumption has been reported at 32.5 mL median weekly [29] or 5 mL/day [30] ; assuming a density of 1.14 ± 0.06 (mean ± SD) g/mL [Supplementary Table 5], 5 mL of e-liquid is approximately equivalent to 5.7 g consumed per day.…”
Section: Resultsmentioning
confidence: 99%
“…All the measured iAs concentrations in this study exceed the CalEPA REL; however, this REL represents continuous exposure, in contrast to the intermittent nature of vaping. The FDA sets permissible daily exposure (PDE) limits for elemental impurities in inhalation medications, in units of µg/day, which can be converted to concentration units of µg/g by dividing by daily dose in grams [28] . MOD e-liquid consumption has been reported at 32.5 mL median weekly [29] or 5 mL/day [30] ; assuming a density of 1.14 ± 0.06 (mean ± SD) g/mL [Supplementary Table 5], 5 mL of e-liquid is approximately equivalent to 5.7 g consumed per day.…”
Section: Resultsmentioning
confidence: 99%
“…This finding has been observed in other studies. 31 , 32 Aherrera et al 33 observed in a cohort study of 150 participants that exclusive ENDS use was associated with more wheezing than nonuse. However, after adjusting for sex, age, and former smoking status, this association was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…68 Assuming a typical respiratory rate of 6 L min −1 , these numbers are translated into exposure limits of 44.4 mg and 140 mg formaldehyde for 1 h and 8 h, respectively. [69][70][71] The exposure to each mL of EJ level is 64% of the 1-hour exposure limit and 20% of the 8-hour exposure limit. We note that this calculated exposure amount is only due to unheated EJ, while intensive vaping or other environmental sources can also contribute to the total exposure.…”
Section: Carbonyl Accumulation In Pure Glycolsmentioning
confidence: 99%